Randomized Face-to-face vs. Home exercise interventions in pregnant women with gestational diabetes. (May 2017) - Symons Downs, Danielle; DiNallo, Jennifer M.; Birch, Leann L.; Paul, Ian M.; Ulbrecht, Jan S.
Abstract: Objectives: Evaluate effects of a theoretically-based, semi-intensive (Face-to-Face; F2F) exercise intervention and minimum-contact (Home) exercise intervention to the standard care (Control) on exercise, its motivational determinants, blood glucose levels, and insulin use of pregnant women with gestational diabetes mellitus (GDM). Design: Randomized control trial with two intervention arms and control (standard care). Method: Participants ( N = 65) were randomized to a Control (standard prenatal care/GDM dietary counseling), Home (standard care + phone education/support + home exercise), or F2F (standard care + on-site education/support + guided exercise with instructor on 2 days/week) group from ∼20 weeks gestation to delivery. Assessments of exercise and motivational determinants were obtained at baseline (20-weeks gestation) and follow-up (32-weeks gestation). Blood glucose levels (fasting/postprandial mg/dL) and insulin use were extrapolated from medical records. Results: At the 32-week follow-up, the F2F group had significantly higher exercise min, pedometer steps/day, and motivational determinants (attitude, subjective norm, perceived control, intention) than controls ( p 's < 0.05) and significantly higher exercise min and subjective norm than the Home group ( p 's < 0.05); these effect sizes were medium-large (η 2 = 0.11-0.23). There was a medium effect (η 2 = 0.13) on postprandial blood glucose at 36-weeks gestation with the F2F group having lower values than controls. Although not significant, the F2F group started insulin later (33 weeks gestation) than the Home (27 weeks) and Control (31 weeks) groups. Conclusion: A theoretically-based, F2F exercise intervention has multiple health benefits and may be the necessary approach for promoting exercise motivation and behavior among GDM women. Highlights: Onsite, structured exercise had a large effect on women's exercise and medium-large effect on motivational determinants. Onsite structured exercise had a medium effect on lowering postprandial blood glucose levels in later pregnancy. Women initiated insulin use later gestation in the structured exercise program compared to the home program and controls. Onsite structured exercise intervention may promote exercise, motivation, and health in women with gestational diabetes.